2023
DOI: 10.3390/land12112039
|View full text |Cite
|
Sign up to set email alerts
|

Paludiculture in Latvia—Existing Knowledge and Challenges

Ilze Ozola,
Iluta Dauskane,
Ieva Aunina
et al.

Abstract: Global climate change impact has increased in recent decades and put urgency on implementing effective climate change mitigation (CCM) activities. Rewetting of drained peatlands is an acknowledged measure to reduce GHG emissions from organic soils in the agriculture and land use sectors. Under waterlogged conditions, decomposition of organic matter in peat decreases, and emissions of CO2 are reduced. Thus, the soil carbon stock is saved, and wet management of the site reactivates carbon sequestration. To reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 23 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Firstly, the retention of existing carbon stored in peat on the total investigation site, which, by our estimates, comprises 14,347.04 t C. If drainage continues, then it poses a risk of releasing stored carbon into the atmosphere, contributing 52,653.64 t CO 2 to the GHG. Secondly, aboveground biomass of reed canary grass, if harvested, could bring 7.9-13.2 t ha −1 that can be used for pellet production [19]. Usage of aboveground biomass is crucial to meet the overall climate benefits, as has been shown by the life cycle assessment for paludiculture practice [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the retention of existing carbon stored in peat on the total investigation site, which, by our estimates, comprises 14,347.04 t C. If drainage continues, then it poses a risk of releasing stored carbon into the atmosphere, contributing 52,653.64 t CO 2 to the GHG. Secondly, aboveground biomass of reed canary grass, if harvested, could bring 7.9-13.2 t ha −1 that can be used for pellet production [19]. Usage of aboveground biomass is crucial to meet the overall climate benefits, as has been shown by the life cycle assessment for paludiculture practice [36].…”
Section: Discussionmentioning
confidence: 99%
“…Both standards use the Greenhouse Gas Emission Site Type (GEST) approach for quantification of greenhouse gas (GHG) emission reduction from rewetted drained peatlands in temperate climatic regions. Due to its experimental nature, we outreached the "Laflora" Ltd. (Jelgavas novads, Latvia) peat extraction company, which is open to such science-to-practice activities (e.g., [18,19]) and made an agreement between Lake and Peatland Research Centre to run the project "Vegetation and water monitoring for paludiculture and carbon sequestration projects at "Laflora" Ltd.". Importantly, the company had no influence on any conclusions or work related to this seven-month project (which lasted from April to November 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Our results revealed that among all studied land use types of peatlands, the mean annual DOC efflux varied from 61.9 ± 4.4 kg ha −1 y −1 in grasslands to 513.1 ± 38.7 kg ha −1 y −1 active peat extraction sites. Silver birch (153.6 ± 11.2 kg ha −1 y −1 ) and Scots pine forests (328.3 ± 23.1 kg ha −1 y −1 ) are common in Latvia, where more than 10% of the total area is covered by peatlands [11,12]. The DOC efflux from Scots pine forests and all peat extraction sites coincided with values from the temperate climate zone, while efflux from silver birch forests, croplands, and grasslands were more comparable to the results from the boreal zone, which contributes to previous findings about the thermal gradient impact.…”
Section: Doc Efflux and Affecting Factorsmentioning
confidence: 99%
“…Lowering the water table by drainage is a prerequisite for peatland forestry, use for agriculture, and peat extraction in most countries [9,10]. These practices are also common in Latvia, where more than 10% of the total area is covered by peatlands [11,12]. As a result, the hydrological regime of the peatlands is altered, and mineralization of peat is promoted, resulting in increased gross C losses.…”
Section: Introductionmentioning
confidence: 99%
“…The common agricultural policy plan determines that large rewetting of organic soils needs to be carried out in order to achieve the reduction in GHG emissions in forestry and agriculture. Also, a reduction in peat extraction for agriculture or forestry is required [11,12]. From strategies for peatland restoration, one of the most used is peatland rewetting in peatland policy.…”
Section: Introductionmentioning
confidence: 99%